PENGARUH KEPERCAYAAN DAN SWITCHING COST TERHADAP LOYALITAS PELANGGAN APOTEK KIMIA FARMA CABANG AHMAD YANI - Alida Putri Delina; Rose Rahmidani (Universitas Negeri Padang, 2018)
: The public awareness of the importance of maintaining health is increasing, and the nature of human body requires it to consume certain medicines to simply maintain health or to cure health complaints is the main reason people buy and consume these medicines. This stimulates the investor to open a business in pharmacy in the city of Padang. The research analyzed the influence of trust on customer loyalty of Kimia Farma Branch Ahmad Yani and the influence of switching cost to customer loyalty of Kimia Farma Branch Ahmad Yani. The population in this study is the customer in Kimia Farma Branch Ahmad Yani. This study obtained F count 74.850 F table 33.1250 on df 2 on the siginfikan 0.0000 <α = 0.05. Based on the result, H0 is rejected and H1 accepted. This means that trust and switching cost have a significant effect to customer loyalty in Kimia Farma.Keyword: Trust, Switching Cost, Loyalty